A Case Report: Airway Obstruction by Ascaris lumbricoides in a Patient with Advanced Laryngeal Carcinoma. Issue 1 (11th August 2020) - Mohammad, Hashim; Kumar, Ajit; Agarwal, Ankit; Pudi, Sivaji
Abstract : Abstract: Ascaris lumbricoides is an intestinal worm that is most prevalent in tropical and subtropical regions, and is usually present with gastrointestinal symptoms in younger age group. The presented case is of a 62-year-old male with stage 4A laryngeal carcinoma hospitalized for chemotherapy, who suddenly developed respiratory distress requiring intubation and ventilator support. The right lung appeared collapsed on chest X-ray. A 15-cm long adult male Ascaris was recovered during suctioning via the endotracheal tube, followed by improvement of oxygenation and reinflation of the lung. The presented case describes a highly unusual ectopic location of adult Ascaris in the respiratory tract, causing sudden onset respiratory distress and airway obstruction that required immediate intubation and critical care unit admission.